Nanochitosan: preparation, characterization and antifungal study - Nguyễn Thị Hiếu Trang; Lê Sĩ Ngọc; Nguyễn Hoàng Thảo Ly; Phạm Thị Hà Vân; Phạm Quang Thắng (Journal of Technical Education Science, 2018)
Nanochitosan particles are synthesized by ionic gelation method using tripolyphosphate (TPP) and protective polyvinyl pyrrolidone K-30 (PVP), and then characterized by particle size determination. The prepared nanoparticles have an average diameters ranging from 40 – 300 nm in solution pH 4.5 and CTS/ TPP weight ratio (6:1). Their physicochemical properties were tested by X-Ray Diffraction (XRD), Field Emission Scanning Electron Microscopy (FE – SEM), Transmission Electronic Microscope (TEM) and dynamic Light Scattering (DLS). After 72 hours, the nanochitosan concentration of 150 ppm inhibited the growth of Phanerochaete salminicolor, Cercospora sp. và Corticium salmonicola Berk. in in vitro was 76.86%, 97.85 and 97.08%, respectively. Nanochitosan product is prepared by ionic gelation method may be potentially used as a high-tech, safe and high antifungal efficiency.